Coping strategies and styles and their relationship to personal wellbeing in a sample of adolescents - Viñas Poch, Ferran; González Carrasco, Mònica; García Moreno, Yolanda; Malo Cerrato, Sara; Casas Aznar, Ferran (Anales de Psicología / Annals of Psychology, 2014)
Several studies have linked coping with personal wellbeing. However, there is no research evidence analyzing this relationship in the Spanish population using Cummins’ model (1997). The aim of this study was to know the level of personal wellbeing of a sample of adolescents and to analyze the relationship between coping strategies and styles and personal well-being. With that purpose in mind, the Personal Well Being Index (PWI) and the Adolescent Coping Scale (ACS) have been administered to a sample of 656 adolescents aged between 11 and 17. The results allow identifying the effect of age and gender on personal wellbeing. Those coping strategies centered on focusing on the positive, physical recreation, working hard and achieving are associated to higher personal wellbeing while self-blaming and keeping to self are with lower personal wellbeing.